Spatial covariance reconstructive (SCORE) super-resolution fluorescence microscopy. - Yi Deng; Mingzhai Sun; Pei-Hui Lin; Jianjie Ma; Joshua W Shaevitz (PLoS ONE)
Super-resolution fluorescence microscopy has become a powerful tool to resolve structural information that is not accessible to traditional diffraction-limited imaging techniques such as confocal microscopy. Stochastic optical reconstruction microscopy (STORM) and photoactivation localization microscopy (PALM) are promising super-resolution techniques due to their relative ease of implementation and instrumentation on standard microscopes. However, the application of STORM is critically limited by its long sampling time. Several recent works have been focused on improving the STORM imaging speed by making use of the information from emitters with overlapping point spread functions (PSF). In this work, we present a fast and efficient algorithm that takes into account the blinking statistics of independent fluorescence emitters. We achieve sub-diffraction lateral resolution of 100 nm from 5 to 7 seconds of imaging. Our method is insensitive to background and can be applied to different types of fluorescence sources, including but not limited to the organic dyes and quantum dots that we demonstrate in this work.